The Duty to Love for the Truth. On the signum specificum of Benedict XVI’s Judicial Petrine Ministry - Pastwa, Andrzej (Philosophy and Canon Law, 2024)
When Pope Benedict XVI crowned with allocution the ministry of Shepherd and Judge in 2013, the final memento so close to his heart, he referred to those who “saveguard truth and justice” — and he did it in a general way, without personal emphasis (somewhat understandably). Only Pope Francis was able, in his first address to the Roman Rota, to show implicitly the genius of his Predecessor’s judicial ministry as Cooperator Veritatis. These circumstances gave rise to a scholarly reflection on the magisterial output of Pope Joseph Ratzinger in question. The primary source giving a comprehensive (and essentially complete) insight into Benedict XVI’s idea of exercising the office of the Church’s supreme judge is a collection of addresses to the Roman Rota from 2006 to 2013. It is in this collection that the very core of the ecclesial ministry at the service of justice can be successfully identified — the ministry whose nature is well reflected by the combination of the formulas: pastor bonus and iustus iudex — according to the personalistic paradigm: in the Church justice and the administration of justice are animated by love (caritas). A methodical study of segments of this original doctrine — through the prism of the principle of sentire cum Ecclesia and the accompanying postulate of harmonization vetera et nova — made it possible to accomplish the research task outlined in the title, namely, an attempt to identify the signum specificum of Benedict XVI’s judicial Petrine ministry.